LEGITIMASI HUKUM ZAKAT DI INDONESIA - Eka Retno Untari; Sariah Mawarni; Aly Hidayat (Mitsaqan Ghalizan, 2023)
This article discusses the legal legitimacy of zakat in Indonesia. In the history of Islam, zakat has been implemented effectively and successfully, even until no more poor people are found entitled to zakat. The teaching of Islam makes zakat a worship of maliyah ijtima’iyah, which has a social goal of building an economic system, has a goal of worldly well-being and the Hereafter. The Zakat is for the poor and the needy. Indonesia as one of the countries with a Muslim majority also accommodates various zakat provisions through several rites of law. This research is a normative law study with a conceptual approach. The results of this study show that the Basic Law of Zakat originates from the Quran, Hadith and National Law, Act No. 38 of 1999 on Zakat Management. Then the presence of BAZNAS, LAZ, and UPZ as part of the implementation of the legitimacy of zakat law in Indonesia.